Effectiveness Of Health Education on Knowledge and Attitude Regarding Diabetes in Type II Diabetes Mellitus Patients in Bengaluru - Ramegowda, Chethana; Hulugappa, Lakshmi (National Journal of Community Medicine, 2016)
Introduction: Considering the importance of Knowledge and positive attitude in preventing severe debilitating complications and controlling diabetes, the present study was undertaken to assess the effectiveness of health education on knowledge and attitude regarding diabetes in Type II Diabetes Mellitus. Materials and methods: The study was conducted from April 2015 to October 2015 among 70 Type II Diabetes Mellitus patients only on oral anti-diabetic drugs. A pre-tested semi-structured proforma was administered and information about socio-demographic profile, and impact of health education intervention was obtained. Results: Most of the subjects were female (80%), in the age group of 35-45yrs (34%), illiterate (40%), unemployed (67%) with Class IV (78%) socio-economic status. The mean ±SD age was 52.47±11.06 years. Significant improvement in knowledge was observed after intervention regarding symptoms, risk factors, complications and maintenance of blood sugar levels. A positive attitude was observed for periodic eye and cardiac examination and were motivated to exercise regularly. Conclusion: There was significant improvement in knowledge and attitude following health education regarding diabetes. Hence it should be an integrated in comprehensive diabetes care.